Integrating Scientific Inquiry in Mathematics Education: Development of a Problem-Based Learning Module to Enhance Mathematical Literacy in Vocational High School Students - Ayu Selvia; I Made Arnawa; Arnellis; Yarman (Postgraduate, University of Mataram, 2025)
This study aimed to develop a valid, practical, and effective Problem-Based Learning (PBL) mathematics teaching module integrated with scientific inquiry to enhance mathematical literacy among Grade X vocational high school students in a Computer and Network Engineering program. The development followed the Plomp model, comprising preliminary research, prototyping, and assessment phases. Data were collected through expert validation, student and teacher response questionnaires, observations, and pre- and post-tests. The module was validated by experts with an average score of 3.607 (very valid), while the student worksheets scored 3.582 (very valid). Practicality was confirmed with a 88.33% score from teachers and 88.40% from students, both categorized as very practical. The module significantly improved students’ mathematical literacy, with an average post-test score of 82.66, reflecting gains in formulating, employing, and interpreting mathematical solutions within real-world vocational contexts. Findings indicate that the integration of scientific inquiry into PBL fosters deeper engagement and strengthens problem-solving skills.